THE EFFECTIVENESS OF Cosmos caudatus IN PREVENTING HYPERGLYCEMIA DUE TO Aeromonas hydrophila INFECTION IN Pangasianodon hypophthalmus - Ronal Kurniawan; Windarti Windarti; Irwan Effendi; Asmika Harnalin Simarmata; Efawani Efawani; Rodhi Firmansyah; Nur Ikhlas Syuhada; Okta Rizal Karsih (Asian Journal of Aquatic Sciences, 2025)
Cosmos caudatus is a herb that benefits overall health. This study aimed to determine the effect of C. caudatus leaf supplementation in feed on blood glucose levels in catfish (Pangasianodon hypophthalmus) challenged with Aeromonas hydrophila. This study was conducted from March to August 2024 at the Marine Microbiology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The method used was an experimental design employing a completely randomized design (CRD) with four treatments and three replications: negative control (NC, no supplementation, no infection), positive control (PC, no supplementation, with A. hydrophila bacterial infection), supplementation with C. caudatus at doses of 10 g/kg (T1), 15 g/kg (T2), and 20 g/kg (T3) of feed, all tested against A. hydrophila. The fish fry used weighed 5.00 ± 1.00 g and were reared for 75 days in 100-L tanks integrated with an aquaponics system. The fish were fed the experimental feed for 60 days before challenge with A. hydrophila bacteria (10⁸ CFU/mL, intramuscular injection) and continued for 14 days after challenge. Blood glucose levels were measured at the beginning (day 1), day 30, pre-challenge (day 60), and post-challenge (day 75). The results showed that adding basil leaves to the feed affected blood glucose (P<0.05). The addition of C. Caudatus leaves maintained glucose homeostasis within the range of 68.33±10.59-79.67±7.77 mg/dL. These findings indicate that C. Caudatus supplementation effectively prevents hyperglycemia caused by A. hydrohila infection in striped catfish and suggest its potential as a natural immunostimulant and metabolic modulator in aquaculture